Work From Home in The Era Covid-19 Pandemic: The Analysis and Impact of It - Suryo Adi Rakhmawan (East Java Economic Journal, 2021)
How many workers in East Java can do their work from home? Is working from home supported by sufficient infrastructure and knowledge? What about workers who cannot do their jobs from home? What are their risks to the economic and health impacts of working outside the home? Then, where should policies be taken to reduce the effects of COVID-19 on the economy, especially the workforce? This study tries to provide answers to some of these questions by analyzing the 2021 National Labor Force Survey data and other secondary data. With the main analytical methods in the form of factor analysis, cluster analysis, and binary logistic regression, this study resulted in the classification of people working with WFH and non-WFH in East Java along with their characteristics in the form of digital needs, income, education, and risk of COVID-19 exposure. Another finding from this study is that people who work with non-WFH, female workers, youth, and low education have a greater tendency to be affected by COVID-19 in their economic activities.